2022
DOI: 10.3389/fpsyg.2022.1049617
|View full text |Cite
|
Sign up to set email alerts
|

On the rocky road to efficient behavior management: Can emotional competencies signal the better way?

Abstract: Self-efficacy beliefs in behavior management (SEBiBM) is a key issue for teachers, while emotional competence is a major contributor to professional success and sustainability in this profession. The investigation of the multifaceted nature of these two constructs may be important in order to take a step toward understanding which emotional competence could foster specific aspects of SEBiBM. To explore this issue, elementary school teachers (N = 121, 1st-4th grades) answered the Profile of Emotional Competence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Additionally, the authors defended that ability EI is a stronger predictor of performance in humanities than in science and that trait EI is a stronger predictor of grades than standardized test scores, though trait EI showed little incremental power over intelligence and personality. EI is also an important factor to foster teachers' well-being (Vesely-Maillefer & Saklofske, 2018) and self-efficacy beliefs (Gay et al, 2022). The results of interventions on emotional competences in students showed that those with higher EI have more advantages than students with lower EI.…”
Section: Ei and School Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the authors defended that ability EI is a stronger predictor of performance in humanities than in science and that trait EI is a stronger predictor of grades than standardized test scores, though trait EI showed little incremental power over intelligence and personality. EI is also an important factor to foster teachers' well-being (Vesely-Maillefer & Saklofske, 2018) and self-efficacy beliefs (Gay et al, 2022). The results of interventions on emotional competences in students showed that those with higher EI have more advantages than students with lower EI.…”
Section: Ei and School Achievementmentioning
confidence: 99%
“…In addition, among the professional competences formally required to perform the job optimally -as indicated in the profile description (training ordinance) -there is "communicating in a way that is appropriate to the recipient and the situation " or "contributing to conflict resolution" for social care workers (SERI, 2016) and "establishing professional relationships with clients and their environment" for healthcare assistants (SERI, 2020), which clearly require emotional competences. More generally, the healthcare assistant and social care worker professions call for a certain level of EI to manage one's own emotions and those of the patient, client, or beneficiary (Dugue et al, 2021;Faguy, 2012;Ingram, 2012;Louwen et al, 2023). In contrast, despite the relevance of EI in many training courses and business sectors, this topic has been very rarely addressed in the VET context, both in terms of vocational school curriculum and interventions meant to improve apprentices' emotional competences.…”
Section: Health and Social Care Training In Switzerlandmentioning
confidence: 99%